Blended Learning as a Solution Study from Home During the Covid-19 Pandemic - Safitri, Meilani; Aziz, M. Ridwan (Proceeding International Conference on Religion, Science and Education, 2022)
The Covid 19 pandemic in Indonesia has been going on for one year. Various policies are made to adapt to changes during the pandemic, one of them is a learn from home program. This article is the result of a review of literature aims to explore blended learning as a solution to learn from home during a pandemic. Based on the literature study conducted, it was found that blended learning was the most appropriate solution to be used in learning during a pandemic.